Optimal performance and emissions of diesel/hydrogen-rich gas engine varying intake air temperature and EGR ratio. (September 2017) - Wu, Horng-Wen; Hsu, Tzu-Ting; He, Jian-Yi; Fan, Chen-Ming
Highlights: We install charge heater, methanol reformer, and cooled EGR into a diesel engine. We study optimal inlet air temperature, aqueous methanol supply rate and EGR ratio. Aqueous methanol supply rate contributes to HC and CO much more significantly. Aqueous methanol supply rate influences smoke emission significantly at 60% load. The maximum reduction is 31.58 % for CO, 41.35 % for NOX and 29.27 % for smoke. Abstract: Having integrated intake air heating system, a steam reforming system, and cooled EGR system into a diesel/hydrogen-rich gas engine, the authors applied the Taguchi approach to determine the optimal intake air temperature, aqueous methanol supply rate, and exhaust gas circulation (EGR) ratio. The intake air temperature is elevated by a heater with an on-off controller. The aqueous methanol supply rate into a methanol steam reformer is changed to produce various flow rates of hydrogen-rich gas introduced into the diesel engine. The cooled EGR is also inducted at the intake port to reduce NOX emission. The optimal operating parameters are found for high BTE (brake thermal efficiency), low CO, HC, NOX, and smoke emissions. Furthermore, performance and emissions at the optimum combined parameters are compared to those at the baseline diesel engine. The results of predictions by using Taguchi approach are further found to agree well with those of confirmation experiments within a 95% level of confidence. The optimal combined parameter can reduce CO emission up to 31.58%, HC emission up to 15.0%, NOX emission up to 41.35%, smoke emission up to 29.27%, and BSFC up to 32.43% and enhance BTE up to 5.13%.